The effects of venture capital syndicate diversity on earnings management and performance of IPOs in the US and UK: An institutional perspective - Chahine, Salim; Arthurs, Jonathan D.; Filatotchev, Igor; Hoskisson, Robert E. (Journal of Corporate Finance, 2012)
This study examines the extent to which principal–principal agency conflicts within venture capital (VC) syndicates lead to additional principal–agent conflicts in IPO firms in two institutional contexts. Using a matched sample of 274 VC-backed IPOs in the US and the UK, it shows that the diversity of a VC syndicate increases pre-IPO discretionary current accruals, used as a proxy for earnings management, but the impact of such diversity is higher in the US. There is also evidence of higher underpricing and lower aftermarket performance in firms with higher earnings management and VC diversity, and these negative performance effects are also higher in the US. Our findings indicate that local and informal institutions have a significant effect on multiple agency conflicts in IPO firms and performance outcomes.